The impact of gamification on the motivation of primary schoolers under martial law - Byhar, Hanna; Pits, Iryna; Shevchuk, Krystina; Prokop, Inna; Шестобуз, Ольга; Дарійчук, Сергій (Amazonia Investiga, 2023)
Ensuring an uninterrupted learning process requires new approaches that will enhance pupil motivation. The aim of the work is to ensure the possibility of including gamification in the learning process of primary schoolers under martial law. This aim was achieved through the use of the methods of questionnaire survey and analysis; calculations of significance, efficiency ratios and Spearman’s rank correlation coefficient. The study found that only 19% of teachers used gamification processes before the study. Learning approaches included core material learning through EdApps and Can’t Wait to Learn. EdApp and Google Form were used to study basic terminology in the form of a game, do homework, and test knowledge. Dynamism is of the greatest importance for teachers, as it promotes the participation of all pupils, and affects the development of independence, thinking, and creative skills. The study found that pupils of grades 2-4, who used gamification in their studies, showed a higher knowledge level. It was established that memory and sociability were developed to the greatest extent among schoolchildren. The practical significance of the work is the possibility of transformation of the educational process as a result of the use of the proposed interactive programmes. Prospects of the research may be related to the comparison of the effectiveness of using gamification techniques among primary and secondary schoolers.
Вплив гейміфікації на забезпечення мотивації учнів початкової школи в умовах воєнного стану
Забезпечення безперебійного процесу навчання потребує нових підходів, які сприятимуть мотивації учнів. Мета роботи полягає у забезпеченні можливості включення гейміфікації у процес навчання учнів початкової школи в умовах військового стану. Для досягнення поставленої мети в роботі були використані методи анкетування, аналізу; розрахунки коефіцієнтів значимості, ефективності й коефіцієнта кореляції Спірмена. В роботі виявлено, що процеси гейміфікації до початку дослідження постійно використовували лише 19% викладачів. Підходи до навчання включали вивчення основного матеріалу за допомогою застосунків EdApp й «Вивчаю не чекаю». Для вивчення основної термінології в ігровому форматі,виконання домашніх завдань, перевірки знань були використані програма EdApp и Google Форма. Для вчителів найбільше значення має динамічність, оскільки сприяє участі всіх учнів і впливає на розвиток самостійності, мислення, творчих навиків. Під час дослідження виявлено, що учні 2-4 класів, які використовували в навчанні процеси гейміфікації, показали більш високу ефективність рівня знань. Встановлено, що серед школярів пам’ять і комунікабельність були розвинена в найбільшій степені. Практичне значення роботи полягає у можливості трансформації учбового процесу в результаті використання запропонованих інтерактивних програм. Перспективи дослідження можуть бути пов’язані з порівнянням ефективності використання прийомів гейміфікації серед учнів початкової і середньої школи.
Keywords: gamification, primary school, group process, game format, pupil motivation, martial law; гейміфікація, початкова школа, груповий процес, ігровий формат, мотивація учнів, воєнний стан